Ultrasound Assisted Ethanolic Extraction of Ipomoea reptans Poir Leaves Antioxidant Activities, Total Phenolic and Flavonoids - Arum, Nabila Setri Sekar; Puspitasari, Anita Dwi (Universitas Negeri Semarang, 2024)
Ipomoea reptans Poir leaves contain phenolic and flavonoid compounds that can reduce free radicals and prevent diseases such as cardiovascular disease, coronary heart disease, and cancer. The drawback of conventional extraction is that it takes a long time, so a shorter extraction method is needed, one of which is the ultrasonic method. This study aims to test the antioxidant activity of ethanol extract of Ipomoea reptans Poir leaves extracted by ultrasonic method and determine the total phenolic and flavonoid content. Ipomoea reptans Poir leaves were extracted using the ultrasonic method at 50oC for 30 minutes with 70% ethanol solvent to obtain ethanol extract of Ipomoea reptans Poir leaves. Antioxidant activity test of ethanol extract of Ipomoea reptans Poir leaves using DPPH method and vitamin C as a comparison. Determination of total phenolic content using gallic acid with a maximum wavelength of 745.20 nm and operating time of 120 minutes. Determination of total flavonoid content using quercetin with a wavelength of 439.60 nm and operating time of 30 minutes. The results showed that the antioxidant activity of Ipomoea reptans Poir leaves obtained an IC50 value of 40.62 ppm (very strong). Total phenolic and flavonoids were 78.33 mgGAE/g extract and 1.03 mgQE/g extract.